Effect of pyrolysis conditions on food waste conversion to biochar as a coagulant aid for wastewater treatment - Yang, Heejin; Kang, Jin Kyu; Park, Seong Jik; Lee, Chang Gu (Journal of Water Process Engineering, 2021)
Food waste (FW) treatment via pyrolysis can be a promising method to reduce the amount of FW and produce value-added products such as biochar. In this study, FW was converted to food waste-based biochar (FWB) as a coagulant aid for wastewater treatment. The solution pH increasing ability of FWB prepared at different pyrolysis temperatures (350, 450, 550, 650, 750, and 850 °C), pyrolysis time (1, 2, 4, 6, and 8 h), and heating rates (5, 10, and 20 °C/min) were compared by mixing biochar and deionized water (1:5 (w/v)) for 30 min, and their physicochemical properties were characterized by FTIR, XRD, and XRF analyses. The optimum pyrolysis conditions for FWB to increase the solution pH were 750 °C, 10 °C/min, and 6 h. Copper coagulation was significantly enhanced as the FWB dose increased along with polyaluminum chloride (PAC). Moreover, the addition of FWB as a coagulation aid improved sludge dewaterability and organic dye removal. Furthermore, the combination of FWB and PAC could also be used to treat industrial plating wastewater containing various heavy metals at different concentrations, which makes FWB a promising coagulation aid.
Keywords: Biochar; Coagulant aid; Food waste; Pyrolysis conditions; Wastewater treatment